Respuesta :

Answer:

[tex](2c+a+3b)(2c-a-3b)[/tex]

Step-by-step explanation:

Given expression:  [tex]4c^2-a^2-6ab-9b^2[/tex]

Factor [tex]-a^2-6ab-9b^2[/tex]

[tex]\implies -(a^2+6ab+9b^2)[/tex]

[tex]\implies -(a+3b)(a+3b)[/tex]

[tex]\implies -(a+3b)^2[/tex]

Factor [tex]4c^2[/tex]

[tex]\implies(2c)(2c)[/tex]

[tex]\implies (2c)^2[/tex]

Therefore,

[tex](2c)^2-(a+3b)^2[/tex]

Difference of Two Squares: [tex]x^2-y^2=(x+y)(x-y)[/tex]

[tex]x^2=(2c)^2\implies x=2c[/tex]

[tex]y^2=(a+3b)^2 \implies y=a+3b[/tex]

Therefore,

[tex]\implies (2c + a + 3b)(2c - (a + 3b))[/tex]

[tex]\implies (2c+a+3b)(2c-a-3b)[/tex]

Answer:

(2c - a + 3b)(2c + a + 3b)

Step-by-step explanation:

4c² - a² - 6ab - 9b²

= 4c² - (a² + 6ab + 9b²) ← the terms in the parenthesiis are a perfect square )

= 4c² - (a + 3b)² ← this is a difference of squares which factors in general as

a² - b² = (a - b)(a + b) , then

= (2c)² - (a + 3b)²

= (2c - (a + 3b) )(2c + (a + 3b) )

= (2c - a - 3b)(2c + a + 3b)

ACCESS MORE